These wilds beyond our fences : letters to my daughter on humanity's search for home - Akomolafe, Bayo (Berkeley : North Atlantic Books, 2017)
"Tackling some of the world's most profound questions through the intimate lens of fatherhood, Bayo Akomolafe embarks on a journey of discovery as he maps the contours of the spaces between himself and his three-year-old daughter Alethea. Told as a series of letters to Alethea in a voice that is by turns poetic, vulnerable, and revelatory--but always engaging--this book describes the daily encounters between the author and his sprightly young daughter, and the failures and redemptions that arise in course of their life together. The book is about giving Alethea a bath, learning to brush her teeth, navigating her demands, concern about her fixation with hand-held devices, watching her refuse to cooperate with her dance instructor, and much more. It is also about the reflections and questions that run through and around their relationship. What does it mean to be a parent? What is our place in this world? Where is our home? Akomolafe's narrative is urgent and unguarded as he discovers that something as commonplace as becoming a father is a cosmic event of unprecedented proportions. Using this realization as a touchstone, he is led to consider the strangeness of his own soul, to contemplate the myths and rituals of modernity, to ask questions about food and justice, to ponder what it means to be human, to evaluate what we can do about climate change, and to wonder what our collective yearnings for a better world tell us about ourselves. These Wilds Beyond our Fences is a passionate attempt to make sense of our disconnection in a world where it is easy to feel untethered and lost. It is a father's search for meaning, for a place of belonging, and for reassurance that the world will embrace and support our children once we are gone"-- (Provided by publisher)
boek